2020
DOI: 10.1111/1744-7917.12777
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference targeting ecdysone receptor blocks the larval–pupal transition in Henosepilachna vigintioctopunctata

Abstract: Henosepilachna vigintioctopunctata is a serious insect pest which attacks a large number of nightshades and cucurbits in Asian countries, Brazil and Australia. Prolonged application of traditional pesticides has caused environmental pollution and exerted deleterious effects on human health. Finding new approaches with high target specificity and low environmental contamination has become an urgent task. RNA interference (RNAi) induced by double-stranded RNA (dsRNA) is expected to be applicable to managing this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…In this study, knockdown of EcRA influenced the expression of genes in the ecdysone signaling pathway. Similarly, the mRNA level of 20E signaling genes was significantly changed after the knockdown of EcR [34][35][36][37][38]. However, the expression of E74 differed from previous research.…”
Section: Discussionmentioning
confidence: 64%
“…In this study, knockdown of EcRA influenced the expression of genes in the ecdysone signaling pathway. Similarly, the mRNA level of 20E signaling genes was significantly changed after the knockdown of EcR [34][35][36][37][38]. However, the expression of E74 differed from previous research.…”
Section: Discussionmentioning
confidence: 64%
“…For example, a recent report demonstrated the efficiency of RNA sprays against Henosepilachna vigintioctopunctata (28-spotted ladybird) in the greenhouse (Wu et al, 2021). Spraying E. coliexpressed dsRNAs targeting the ecdysone receptor (EcR) gene onto the foliage of greenhouse-growing potato plants provoked the death of third and fourth instar larvae and reduced leaf damage (Wu et al, 2021). Confirming these results, another study showed exogenous dsRNA application as a promising alternative to chemical pesticides for controlling H. vigintioctopunctata (Lü et al, 2021).…”
Section: Significant Advances Of Rna Spray Controlling: Insectsmentioning
confidence: 91%
“…In addition to the control of viruses and fungi, insect pests are also generally accessible to RNA sprays (Table 1). For example, a recent report demonstrated the efficiency of RNA sprays against Henosepilachna vigintioctopunctata (28-spotted ladybird) in the greenhouse (Wu et al, 2021). Spraying E. coliexpressed dsRNAs targeting the ecdysone receptor (EcR) gene onto the foliage of greenhouse-growing potato plants provoked the death of third and fourth instar larvae and reduced leaf damage (Wu et al, 2021).…”
Section: Significant Advances Of Rna Spray Controlling: Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular resources for H. vigintioctopunctata have only recently been developed (Guo et al, 2019;Zhang et al, 2018). Moreover, it has been documented that dsRNA can successfully knock down target genes in H. vigintioctopunctata (Hashiro et al, 2019;Ohde et al, 2009;Wu et al, 2020). This offers a great opportunity to explore the molecular mechanisms of white gene(s) by RNAi.…”
Section: Introductionmentioning
confidence: 99%